Case report of a pacient with supposed Frontonasal Dysplasia: The complexity of diagnosing (Research, Society and Development, 2024)
Frontonasal dysplasia represents a set of malformations that affect the eyes, nose and frontal region of the face. In this study, the objective was to report the clinical case of a 46,XY male patient, who presented characteristics of frontonasal dysplasia, with malformations of the face and skull, as well as the difficulty of correct diagnosis. The patient presented with congenital malformation of the neural tube (sphenoethmoidal encephalocele), agenesis of the corpus callosum, infantile spasm, chorioretinal scar, craniofacial anomalies including: incomplete median preforamen cleft, rare Tessier cleft 0-14, colpocephaly, midface retrusion, anteverted nostril; delay in motor development, reduced visual acuity (convergent strabismus in the left eye), dysphagia in the oral phase, telangiectasias in the cheeks and posterior portion of the leg, autism, phimosis, neurogenic bladder, varus foot corrected with a splint. The etiology has not been defined, due to the diagnostic complexity and accessibility to genetic tests, but the patient presents a well-defined condition within the spectrum of frontonasal dysplasias: agenesis of the corpus callosum, basal encephalocele, ocular anomalies and midline fissure. In this case, genetic counseling provides the family with accessible knowledge about the condition so that it can contribute to empowerment and access to treatments that improve the patient's overall health.